Robots won't save Japan : an ethnography of eldercare automation - Wright, James, 1984- (Culture and politics of health care work., 2023)
"The book is an anthropological examination of the Japanese government's ongoing attempts to develop and implement robots as a solution to its crisis in elder care"--